Beyond Citations: Successes and Challenges in Using Zotero for International Student Collaboration - Sara Kern; Lynn Cockett (Pennsylvania Libraries: Research & Practice)
This article shares how a team of a librarian and two professors worked together to develop, implement, and support students through a collaborative project for two Communication courses, one in the United States and one in the Czech Republic. In this project, students learned to use Zotero Groups for resource sharing, and sharpened their skills to discover, assess, and contextualize a broad spectrum of media sources. The class was experimental, and the use of Zotero did not go as smoothly as planned. This provided us with additional insights into how use of the tool might work better in the future. We share the success and challenges of that process, with recommendations for future projects.